Impact of Fluctuating BI 7-Day Reverse Repo Rate Movement on Jakarta Composite Index Value: Date-Regular Frequency Data - Yandes, Jufri; Destiana, Destiana (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
A study was conducted to explore the impact of fluctuating BI 7-Day Reverse Repo Rate (BI7DRR) movements on the value of Jakarta Composite Index (JCI) in the Indonesian capital market using statistical techniques, focusing on understanding existing knowledge gaps. Through experiments using Date-Regular Frequency data type in linear regression analysis for the period of January 2023 (2023M01) to December 2023 (2023M12). The data has passed the normality, heteroscedasticity, and autocorrelation tests, this study showed that there's a pretty big impact of BI7DRR on JCI, especially when it comes to the fluctuating movement. The results of the analysis show that the volatile movement of BI7DRR has a measurable impact on the value of JCI, reinforced and supported by the results of previous studies whose results can strengthen the findings with a positive constant regression coefficient and supportive hypothesis test results. The results obtained are expected to provide valuable insights for investors, market analysts, and especially policy makers on how the fluctuating movement of BI7DRR can affect the dynamics of the stock market in Indonesia, especially the value of JCI in order to maintain a sustainable economy.